Lower Risk of Intracranial Arteriovenous Malformation Hemorrhage in Patients With Hereditary Hemorrhagic Telangiectasia. Issue 5 (May 2016) - Yang, Wuyang; Liu, Ann; Hung, Alice L.; Braileanu, Maria; Wang, Joanna Y.; Caplan, Justin M.; Colby, Geoffrey P.; Coon, Alexander L.; Tamargo, Rafael J.; Ahn, Edward S.; Huang, Judy
Abstract : BACKGROUND: Patients diagnosed with hereditary hemorrhagic telangiectasia (HHT) are at risk of developing intracranial arteriovenous malformations (AVM). However, the clinical manifestations and natural history of HHT-related AVMs remain unclear due to the rarity of these lesions. OBJECTIVE: To clarify the clinical characteristics and hemorrhagic risk in HHT-related AVMs. METHODS: We performed a retrospective review of all patients diagnosed with both HHT and intracranial AVMs who were evaluated at our institution from 1990 to 2013. Patients with missing data or lost to follow-up were excluded. Baseline characteristics and subsequent hemorrhagic risk were evaluated. RESULTS: In an AVM database of 531 patients with 542 AVMs, a total of 12 HHT patients (2.3%) with 23 AVMs were found. Mean age at diagnosis was 36.5 years, with 41.7% male. Compared to patients with sporadic AVMs, patients with HHT were less likely to present with ruptured AVM ( P = .04), headaches ( P = .02), and seizures ( P = .02), and presented with better modified Rankin scores ( P < .01). HHT-related AVMs were smaller in size ( P < .01), of lower Spetzler-Martin grade ( P = .01), and had less temporal lobe involvement ( P = .02) compared to sporadic AVMs. Six HHT patients (50.0%) were found with multiple intracranial AVMs. One hemorrhage was found during an observation period of 149.6 patient-years and 297.5 lesion-years, translating to 1.3% per patient per year or 0.7% per AVM per year. CONCLUSION: HHT-related AVMs are smaller in size with lower Spetzler-Martin grade and less temporal lobe involvement than sporadic AVMs. Patients with HHT frequently present with multiple intracranial AVMs. Conservative management is generally recommended due to lesion multiplicity and relatively low hemorrhagic risk. ABBREVIATIONS: AVM, arteriovenous malformations HHT, hereditary hemorrhagic telangiectasia ICH, intracranial hemorrhages